Marketing Planning Research on the Integration of Regional Culture into Milk Tea Products: A Case Study of Yongjia County - Su, Huiyi; Shou, Keyi; Chen, Gaoxiang; Yu, Tanzhun; Shou, Keyi; Fu, Jingping; Ma, Yuxing (International Journal of Social Sciences and Public Administration, 2024)
This paper proposes that Yongjia culture, an indigenous regional culture of Wenzhou, possesses profound historical roots and unique cultural charm. In recent years, with the rise of milk tea products, an increasing number of young people choose to enjoy a cup of milk tea during their leisure time. This marketing planning adopts story-based marketing by integrating distinctive Yongjia cultural elements into milk tea products, introducing a city-exclusive beverage made from the local specialty, Wuniu Early Tea. Through online promotion on platforms like Douyin and Xiaohongshu for new product previews and event announcements, as well as establishing offline themed stores infused with Yongjia cultural elements, offering limited-edition collaborative packaging featuring a special logo, and accompanying promotional videos, the strategy aims to attract customers, enhance brand image, and promote Yongjia’s local culture.